Tāhlīlu Āsālībā Tā’ālumī āt-Thullābāh Mā’ārīf Metro fīī ād-Dārsī āl-Lughoh āl-Ārobīyāh - Oktafia, Anita; Syaifullah, Muhammad; Agus Mushodiq, Muhamad; Abushihab, Eiman F. (CV. Creative Tugu Pena, 2024)
This article aims to analyze student learning styles to help students recognize and develop their learning potential to the maximum. Learning Style is an easy way to absorb, manage, store and apply information. By knowing one's learning style, one can help the effectiveness of learning, maximize learning potential, increase self-confidence, and adapt learning according to individual needs. This research is qualitative in nature using descriptive analysis methods. Data collection was carried out through observation, interviews, learning style questionnaires and documentation. The number of samples taken was 24 students determined using purpose sampling techniques. Sources of information were obtained from survey results regarding learning styles, and interviews obtained from students. After analysis, the results show that students have a preference for visual learning more than other learning styles. Based on several factors, including more responsive visual learning materials, ease of understanding, ability to visualize vocabulary, use of interactive media and learning creativity. Having these four factors makes learning easier for students who have a visual learning style to accept. Thus, it can be concluded that understanding student learning styles and their use in learning Arabic can improve student learning achievement well. However, it needs to be acknowledged that this research has several weaknesses. Therefore, the author hopes that there will be further research that can explore how to identify individual learning styles to ensure optimal learning.